Predicting child socioemotional competence : the role of different forms of parental control and warmth - Özyol, Beyza. (Thesis (M.A.) - Bogazici University. Institute for Graduate Studies in Social Sciences, 2023., 2023)
The current study focuses on the role of parental control and warmth on child socioemotional competence. Therefore, this study examined how maternal control (i.e., parental monitoring, structuring, psychological control, and culturally valued parental control) and warmth relate to school age children's social and emotional functioning based on self-report from a sample of Turkish mothers. Participants were 213 mothers of children (112 girls and 101 boys) between 7-18 years. Participants were administered a battery that consist of a demographics form and various scales regarding parenting practices and child outcomes. Data was analyzed using principal component analysis, bivariate correlation, and hierarchical multiple regression. Findings revealed that maternal psychological control was related to lower prosocial behaviors and higher child internalizing symptoms; however, it was not associated with child externalizing problems. Parental structuring was only found to be positively related to higher prosocial behaviors. Parental monitoring was linked to lower child internalizing problems and higher prosocial behaviors; however, it was not related to child externalizing problems. Culturally valued parental control was associated with higher child internalizing, externalizing problems, and lower prosocial behaviors, addressing the importance of examining culture-specific parental practices. Lastly, parental warmth was only associated with higher prosocial behaviors.
Keywords: Emotional problems of children.; Parent and child.